Today situation of after degree education in the Siberian State Medical University - E. L. Timoshina; V. M. Alifirova (Бюллетень сибирской медицины)
In the article the modern situation of the post degree courses of the medical workers in the Siberian State Medical University are presented, also the problems of the post degree medical education and the achievements of SSMU in this sphere of this activity are considered and pointed out.